Controlling the photoperiod to raise the melatonin content of sheep milk. Photoperiod control and milk melatonin content - Keskin, M; Gül, S; Karaaslan, İ; Yakan, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to determine the effect of changing photoperiod time on the melatonin content of sheep milk. The animal material of the study consisted of 40 heads of Awassi sheep that gave birth in May 2021. The sheep were given roughage containing dry matter with 2.5% of their body weight and concentrated feed (2400-2600 kcal ME and 15-16% Crude Protein) as the 40% of their milk yield each day during the lactation period. The experimental ewes were randomly assigned into two groups with 20 animals in each. While the control group sheep were managed with normal day-time length during the lactation, the photoperiod restriction group were kept in the shed with 16 hours of darkness and 8 hours of daylight for 2 months. At the end of the two months, ewes of the both groups were managed in normal daylight until the end of lactation period. During the photoperiod restriction term, milk samples were taken at an interval of 15 days, while the milk composition was determined by a milk analyser and melatonin contents were determined by using LC MS/MS. In addition, lactation milk yield and lactation periods were estimated for all sheep. Statistical evaluation of the obtained data was done by using the SPSS package program. At the end of the study, the application of the extended dark period was found to be affected milk yield (P<0.05) as well as melatonin amount in the milk (P<0.001). Significantly higher melatonin amount was observed in the milk of sheep kept in a long-term dark environment compared to those exposed to normal photoperiod (11.1±7.24 pg/ml vs 6.1±4.55 pg/ml; P<0.001). As a result, it was determined that the prolonged dark period during a day increases the milk melatonin content. It can be also stated that the sheep's milk to be produced with this application could be a product that could take place in the functional food market.